2017
DOI: 10.1186/s13256-017-1230-6
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas oryzihabitans sepsis in a 1-year-old child with multiple skin rashes: a case report

Abstract: Background Pseudomonas oryzihabitans is a Pseudomonas bacterial organism rarely implicated in human infections. The bacterium has been isolated in a few reported cases of neurosurgical infections and patients with end-stage cirrhosis, sickle cell disease, and community-acquired urinary tract infections. Limited information exists in developing countries, however, because of the lack of advanced microbiological tools for identification and characterization of this bacterium. This case report describes the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Our patient was treated by piperacillin/tazobactam, imipenem, and ceftazidime. The former reports confirmed that imipenem and ciprofloxacin are the first therapeutic choices for P oryzihabitant infection …”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Our patient was treated by piperacillin/tazobactam, imipenem, and ceftazidime. The former reports confirmed that imipenem and ciprofloxacin are the first therapeutic choices for P oryzihabitant infection …”
Section: Discussionmentioning
confidence: 63%
“…This bacterium is not human normal-flora and numerous reports suggested that the bacterium's transition is through environment. [2][3][4] According to previous reports, the frequency of cutaneous infection due to P oryzihabitansis is 0.097%. Tena et al reported six cases of skin infected with this bacterium from surgical wounds, cutaneous abscess.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations